Criminal Liability for Dangerous Challenge Content on Social Media Causing Accidents from the Perspective of the New Criminal Code - Endang Yuliana Susilawati; Kartika Asmanda Putri; Supriyanta Supriyanta; FX. Hastowo Broto Laksito; Isabel Naftali Fabian Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of social media has given rise to the phenomenon of digital challenges, which in practice are not only entertaining but also have the potential to cause accidents, serious injuries, and even death. This condition raises legal issues regarding the criminal liability of both the creators and disseminators of dangerous content on social media. This research aims to analyze criminal liability for perpetrators of social media challenge content that causes accidents and to examine the problems of law enforcement and criminal law policy regarding harmful content in the digital space. The research uses a normative juridical method with a legislative approach and a conceptual approach thru the analysis of Law Number 1 of 2023 on the Criminal Code, Law Number 1 of 2024 on the Second Amendment to the Electronic Information and Transactions Law, as well as other related regulations. The research results show that criminal liability for social media challenge content creators can be constructed thru provisions regarding negligence, criminal participation, and the dissemination of electronic information that harms the public. However, law enforcement still faces various obstacles, such as the absence of specific regulations regarding harmful content, difficulties in proving causal relationships, and weak supervision of digital platforms. Therefore, there is a need for an update to the criminal law policy that is more adaptive and comprehensive in order to provide legal protection to society in the digital era.